Developing Afghanistan Media and Possibility of Citizen Journalism - Osman Köroğlu (Online Academic Journal of Information Technology, 2011)
Afghanistan has witnessed the activities in the field of journalism since 1900. However, the country's media sector, during the wars, political crises and uncertainty, did not show a consistent growth and development until today. With the government of Hamid Karzai, rapid and large-scale freedom and progress in the media can be seen. However, Afghanistan must put forward its own style of the media and original reporting practices. For this purpose, she should take support of other countries and civil society organizations at least for now. In this context, one can hope to assume that educational institutions in the country will have important roles in shaping the present and future of developing media in Afghanistan. Similarly, if the basic technological infrastructure and education is provided, new communication technologies can provide the rapid development of alternative types of journalism in Afghanistan like participatory journalism and citizen journalism.